ANALISIS TINGKAT KESEGARAN JASMANI PESERTA DIDIK DITINJAU DARI SARANA PRASARANA PENDIDIKAN JASMANI DI SEKOLAH DASAR NEGERI MARTAPURA KABUPATEN BANJAR - Effendi, Muhammad Miftah; Hamid, M. Kusaini, Abd. (MANGGUREBE: Journal Physical Education, Health and Recreation, 2021)
This study aims to know how the level of physical fitness of a student in terms of physical education facilities in SDN Martapura, Banjar Regency. The method is a combination method (mixed method) with data collection techniques by measuring what needs to be measured and observed. And also for its population totaling 226 students, but only 32 samples were taken from 10 - 12 years old, consisting of Keramat State Elementary School, Sungai Batang 1 State Elementary School and Central Malay State Primary School Martapura Regency Banjar. The final results of this study were obtained from the Keramat State Primary School with a sample of 17 students, 2 students (11.76%) moderate classification (S), 9 students (52.94%) less classification (K) and 6 students (35.50%), very poor classification (KS). Sungai Batang State Elementary School 1 sample size is 6 students, 1 student (16.67%), medium classification (S), 2 students (33.33%) poor classification (K), 3 students (50.00%) very less calcification (KS). Central Malay State Elementary School sample number 9 students, 1 student (11.11%) classification is medium (S), 5 students (55.56%) classification is less (K), 3 students (33) , 33%) poorly calcified (KS)